Eksplorasi Praktik Deep Learning dalam Pembentukan Karakter Religius Siswa di Sekolah Dasar - M Choirul Muzaini; Syahrul Aziz (CV. Lentera Literasi Indonesia, 2026)
This study aims to explore the practice of deep learning in Al-Qur'an learning and its contribution to the formation of religious character in elementary school students. The study was conducted at SD Negeri 1 Jatidatar, Bandar Mataram District, Central Lampung Regency, with a focus on the use of sound wave analysis media in Al-Qur'an reading learning. The research approach used was qualitative with a case study type. The research subjects included Islamic Education teachers and fourth and fifth grade students. Data were collected through participatory observation, in-depth interviews, and documentation, then analyzed using thematic analysis. The results showed that sound wave analysis-based learning encouraged students to actively engage in the learning process through activities such as observing, comparing, analyzing, and reflecting on reading errors. This practice not only improves the accuracy and precision of reading the Qur'an, but also contributes to the formation of students' religious character, such as discipline, honesty, responsibility, self-reflection, and perseverance. The integration of deep learning with simple technology has proven to be capable of creating meaningful and contextual Islamic Religious Education learning. This research provides a theoretical contribution to the development of deep learning in Islamic education as well as a practical contribution in the form of an innovative learning model that can be applied in elementary schools.